Regaining power: How feelings of exclusion during COVID-19 are associated with radicalism among critics of containment policies - Pfundmair, Michaela; Mahr, Luisa A. M. (Frontiers in Psychology, 2022)
Past experimental research has shown that social exclusion can be linked with radicalism. During the COVID-19 pandemic, feelings of social isolation and loneliness rose, just like protests and violence against national anti-COVID-19 measures did. Based on these observations, we hypothesized that feelings of exclusion induced by measures to contain the spread of COVID-19 were associated with radicalism intentions to illegally and violently fight COVID-19-related regulations among critics of the containment policies (Hypothesis 1). Moreover, we expected that radicalism intentions against COVID-19-related regulations fortified needs deprived by social exclusion (Hypothesis 2). Studying a sample of individuals who opposed the measures to contain the spread of COVID-19 (N = 171), we found evidence for both hypotheses: Results revealed that feelings of social exclusion induced by COVID-19 containment measures predicted radicalism intentions. Moreover, the relationship between exclusion and radicalism was associated with fortifying power issues. Political opinion did not moderate these effects. These data replicate the exclusion-radicalism link in the COVID-19 crisis and add one more factor that may have promoted radical developments during that time. Fortifying feelings of power, radicalism appeared to foster well-being, though at a high political price.